RESPON PETANI TERHADAP APLIKASI PUPUK ORGANIK CAIR BIOURIN PADA TANAMAN BAWANG MERAH DI DESA NOELBAKI KECAMATAN KUPANG TENGAH - Rupa Matheus; Donatus Kantur; Anisden Baru Bangngu (Partner, 2023)
The purpose of this study was to determine the response of horticultural farmers and the factors related to the response of vegetable farmers in Noelbaki village to adopting Biourin cattle fertilizer which is enriched with indigenous microbes. This study uses the action research method through a demonstration plot approach. The technology being disseminated is cow biourin fertilizer which has been enriched by indigenous microbes which is applied to shallot plants. The research involved vegetable farmers who are members of the Petra Farmers Group, which totals 30 people. The research began with counseling and making demonstration plot gardens as learning media for farmers. The data analysis technique used is descriptive analysis and Rank Sperm correlation analysis. The results showed that in general, the average response of vegetable farmers after dissemination of biourin fertilizer was in the high category with a score of 2.60, which means that the respondent farmers accepted and acknowledged the superiority of biourin fertilizer. Keywords: Farmer response, POC of cow biourin; indigenous microbes